Magnetic characterisation of strain ageing in near eutectoid drawn pearlitic wire using an electromagnetic (EM) sensor. (January 2022) - Jones, B.L.; Jolfaei, M.A.; Hobson, S.; Rainforth, W.M.; Davis, C.L.
Highlights: The electromagnetic sensors are capable of detecting strain ageing in near eutectoid pearlitic wires. Electromagnetic sensors are a non-destructive monitoring technique, which may lead to in-situ sensors. The development of In-situ sensors could extend service life of components. Abstract: High carbon steel wires are susceptible to a detrimental ageing process, known as strain ageing. Strain ageing is responsible for the redistribution of carbon atoms within a wire microstructure. The redistribution of carbon atoms results in changes to the mechanical properties of a wire in service, which can lead to premature failure. Current methods of monitoring strain ageing are destructive, making in service monitoring challenging. Therefore, it is desirable to detect these subtle changes in a non-destructive manner. This paper reports trials of an electromagnetic (EM) sensor designed for monitoring wire samples. It is known that EM sensors are sensitive to microstructural changes in steels, and sensors are being used to monitor phase transformations during hot steel processing and strip properties in cold mills. This is the first reported use of an EM sensor for monitoring strain ageing in high carbon steel wire. Wires were tested using current standard methods (mechanical testing) alongside EM sensor measurements. An initial increase in tensile strength was observed via mechanical testing, whilst the EM sensors measured a corresponding change in real inductance. In more severe ageing conditions, mechanical properties levelled off somewhat, which was also measured in the corresponding EM sensor measurements. EM sensors are capable of detecting the subtle changes caused by strain ageing in a non-destructive manner. Therefore, the development of inline EM sensors have the potential to monitor strain ageing in a level of detail which has not been reasonably achievable with currently available testing methods.